Exposure to mercury in dentistry: A safety concern - Shetty Pushparaja; Shetty Akshatha (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: Mercury is a heavy metal and overexposure to mercury may have a toxic effect on the nervous system, renal system, reproductive system, immune system and on motor activity. In dentistry, mercury is used along with metals in amalgam restorations. Studies have shown that mercury consistently releases from amalgam restorations. There is a controversy regarding this released mercury having any toxic effect on human beings. The aim: The aim of this work was to highlight the adverse effect of silver amalgam restoration and create awareness among all. Conclusion: Amalgam is still widely used as restorative material due to its excellent physical properties. Because of its environmental impact, mercury must be kept away from all users, including dentistry.